(untitled) (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2012)
Indian Pharmaceutical Market has remained consistently progressive over the decade. The two major contributing parameters of the Industry doctors and patients, were also increasing in numbers and thus adding to the growth of the industry. Due to this continuous growth character of the Industry, the Industry has always remained one of the most attractive business sectors. New players continue to enter the market while the old and existing pharmaceutical companies consolidate their respective business simultaneously. Therefore, Indian Pharmaceutical Market (IPM) is also one of the most competitive market cluttered with too many players (more than six hundred registered pharmaceutical companies) and represented by too branded generic products. The main criterion of success in business in IPM is not just overall sales turnover growth but how to achieve sales growth higher than the market sales growth and at the same time ensure increasing profitability. Intellectual Property Rights were introduced since January 2005, however all most all generic molecules have significant number of participants, with very few patented formulation available in the market, at present. In such a market condition one would necessarily require sharper focus for effective execution. Therefore one would essentially require developing long term and short-term strategic marketing action plan for facilitating effective implementation. To formulate effective strategy one would require studying the market dynamics critically and then develop the required strategy based on the individual organization strengths and weakness. Based on medical doctors prescription habit analysis and particular pharmaceutical marketing company product wise sales data analysis, in this article we have discussed how an unique strategy formulation tool Product Prioritization Matrix (PPM) can be developed, which can be effectively used for strategic product portfolio planning and management. Effective application of PPM would result in faster sales growth and optimize organization profitability.